1998
DOI: 10.1212/wnl.50.4.1033
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proton-decoupled 31 P MRS and 1 H MRS in the evaluation of Huntington's and Parkinson's diseases

Abstract: Previously described failure of global energy metabolism in HD was not confirmed. However, quantitative 1-hydrogen MRS and decoupled 31-phosphorus MRS are sensitive to +/-10% alterations in key cerebral metabolites, and may be of value in noninvasive monitoring of appropriate therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
98
0
2

Year Published

1999
1999
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(106 citation statements)
references
References 14 publications
6
98
0
2
Order By: Relevance
“…The CrϩPCr signal thus reflects the state of systemic energy use and storage (Stockler et al 1996;Valenzuela and Sachdev 2001). The reduction in CrϩPCr is, in effect, considered to be associated with cellular energy impairment (Hoang et al 1998;SanchezPernaute et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The CrϩPCr signal thus reflects the state of systemic energy use and storage (Stockler et al 1996;Valenzuela and Sachdev 2001). The reduction in CrϩPCr is, in effect, considered to be associated with cellular energy impairment (Hoang et al 1998;SanchezPernaute et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when patients were grouped based on clinical criteria, neural networks could be trained to classify spectra into these groups and controls to a relatively high degree. Published 1 H MRS results suggest that there are generally no dramatic differences in metabolite concentrations between PD patients and controls (5)(6)(7)(8)23,24). Furthermore, where differences do exist, they are frequently not sufficient to enable classification of individuals from a data set of patients and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, where differences do exist, they are frequently not sufficient to enable classification of individuals from a data set of patients and controls. For instance, Hoang, et al (5) concluded that while small, systematic abnormalities in NAA (decreased), Cr (decreased), and Cho-containing compounds (increased) were evident, they were insufficient to make diagnosis possible in an individual patient. Davie, et al (6) found that only one of nine patients exhibited a markedly reduced NAA/Cr ratio compared with a control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…104 Animals have a quantifiable motor deficit, but the characteristic Lewy bodies observed in human patients are not seen, and there is nonspecific toxin-induced damage to neighboring neurons. This model has been particularly useful for pharmacological screening but does not replicate many key 75 Tkac et al, 148 Pfeuffer et al, 74 Govindaraju et al 73 Spinocerebellar ataxia Huntington's disease Characterization of the metabolite perturbations and impaired energy metabolism in PD Hoang et al, 79 Jenkins et al 28,81 Metabolic characterization of toxin-induced and transgenic animal models of HD Tsang et al, 76 Jenkins et al, 121 van Dellen et al, 120 Dautry et al 113,149 Evaluation of creatine supplementation in HD models and patients…”
Section: Preclinical Metabonomic Studiesmentioning
confidence: 99%